Chicken genome modelling for the benefit of science. Issue 1 (March 2016) - STUPAR, M.; VIDOVIĆ, V.; LUKAČ, D.; PUVAČA, N.
Abstract : In the early 21st century, genetic modification of chicken primordial germ cells (PGCs) had not been possible before their transfer and recovery through germ line. Chicken PGCs resist deliberate genetic modification, probably by silencing the transgenes in the genome. The use of mobile genetic elements (transposons) in genetic modification and germ-line transmission of PGCs has recently overcome this problem, so that PGCs can be used for further chicken genome modelling in order to study developmental biology, non-coding RNA (ncRNA) functions, viral DNA-RNA hybridisation, silencing of transgene expression, together with epigenetic modification, and gene function. Application of the transposons, viral integrase, zinc-finger nuclease and site-specific recombinase in whole genome elucidation is not sufficient. The chicken PGCs can be used as a model of choice to establish a new generation of methodology for genome modelling. For this purpose the livesome vectors are proposed.